2015
DOI: 10.1148/radiol.14140773
|View full text |Cite
|
Sign up to set email alerts
|

The Power Button Sign: A Newly Described Central Sulcal Pattern on Surface Rendering MR Images of Type 2 Focal Cortical Dysplasia

Abstract: Given its excellent reproducibility and specificity, the PBS, when present, could become a useful qualitative diagnostic MR criterion of FCD2 in the central region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…A combination of cortical thickening, gray–white blurring, and transmantle sign was found in all 59% of patients with FCD II who had a positive MRI . A specific aspect of the central sulcus appearance named “power button sign” was found in 62% of FCD II patients in a case‐control study and was considered highly specific for this type of dysplasia . Our results support a study that analyzed pathologic specimens from 13 patients with FCD who had en bloc resection with a 7T magnet; 85% of patients had ETLE.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A combination of cortical thickening, gray–white blurring, and transmantle sign was found in all 59% of patients with FCD II who had a positive MRI . A specific aspect of the central sulcus appearance named “power button sign” was found in 62% of FCD II patients in a case‐control study and was considered highly specific for this type of dysplasia . Our results support a study that analyzed pathologic specimens from 13 patients with FCD who had en bloc resection with a 7T magnet; 85% of patients had ETLE.…”
Section: Discussionsupporting
confidence: 82%
“…32 A specific aspect of the central sulcus appearance named "power button sign" was found in 62% of FCD II patients in a case-control study and was considered highly specific for this type of dysplasia. 33 Our results support a study 34 that analyzed pathologic specimens from 13 patients with FCD who had en bloc resection with a 7T magnet; 85% of patients had ETLE. The authors found isolated gray-white blurring in the four patients who had FCD IIa and hypothesized a less severe neuroradiologic feature when compared to FCD IIb, owing to the absence of edema, balloon cells, and myelin alteration.…”
Section: Explanation and Importance Of Temporal Tip Abnormalitiessupporting
confidence: 84%
“…Subtle signal changes can be obvious in one plane but completely obscured by the cortical anatomy in another plane. In some cases, even, the sole identifier can be an abnormal gyration pattern, only recognizable in high‐quality 3D image sets …”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Mellerio et al, using a post-processing tool for 3D visualization of brain sulci, assessed central sulcus variants and particularly a sulcal pattern “power button sign” (defined as the interposition of a precentral sulcal segment between the central sulcus and one of its hook-shaped anterior ascending branches) in 37 patients with histologically proven FCD type II of the central region and 44 healthy control subjects [42]. Their data suggest that central sulcus with the FCD type II patient group present with significantly more side branches and connections with the precentral sulcus and sylvian fissure.…”
Section: Mri Post-processing For Sulcal Morphologymentioning
confidence: 99%